2021
DOI: 10.1016/j.jelectrocard.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS on surface electrocardiography as a predictor of cardiac mortality in patients with SARS-CoV-2 infection

Abstract: Aims Although severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection is mainly a respiratory system disease, recent studies reported that cardiac injury is associated with poor outcomes in this population. There are few studies which assessed standard electrocardiogram (ECG) as a prognostic tool during the course of SARS-CoV-2 infection. The aim of this study is to identify the relationship between of ECG parameters and prognosis of patients infected with SARS-CoV-2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(14 reference statements)
0
10
1
Order By: Relevance
“…In this study, similar to our results, hospitalization duration, ICU requirement, all-cause mortality, and cardiac mortality were found to be higher in patients with COVID-19 with f-QRS. However, this study revealed that there was a positive relationship between QRS duration and duration of hospital stay, need for ICU, and mortality, but there was no relationship between T inversion and mortality (39). In contrast, no relationship was found between QRS duration and mortality in our study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In this study, similar to our results, hospitalization duration, ICU requirement, all-cause mortality, and cardiac mortality were found to be higher in patients with COVID-19 with f-QRS. However, this study revealed that there was a positive relationship between QRS duration and duration of hospital stay, need for ICU, and mortality, but there was no relationship between T inversion and mortality (39). In contrast, no relationship was found between QRS duration and mortality in our study.…”
Section: Discussioncontrasting
confidence: 89%
“…Especially in patients with COVID-19, f-QRS may be a predictor of poor clinical outcomes. In a recently published paper, Yildirim et al (39) studied 114 patients with COVID-19. In this study, similar to our results, hospitalization duration, ICU requirement, all-cause mortality, and cardiac mortality were found to be higher in patients with COVID-19 with f-QRS.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, we found fragmentation of the QRS in 79% of patients, whereas previously, fragmented QRS was identified in 36.8% of patients and was a predictor of cardiac mortality in patients with COVID-19. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Many small studies have shown associations between ECG abnormalities and outcome. In a retrospective study including 114 patients with COVID-19, QRS duration and presence of fQRS were associated with all-cause and cardiac mortality [17] . Using the same criteria they reported fQRS in 36.8% of patients, whereas in our population fQRS was present in 20.2%.…”
Section: Discussionmentioning
confidence: 99%